1994
DOI: 10.1080/07315724.1994.10718377
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin B6 status of strength and speedpower athletes.

Abstract: Vitamin B6 status can be quantified using the weighed food record, microbiological whole blood determination, and 4-PA excretion; however, limits of the individual methods must be taken into account. Vitamin B6 supply of the athletes still cannot be definitively assessed because there are no generally valid reference values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Similar results were reported by Fogelholm et al [10], although the α EAST values obtained by them were higher than in this study. On the other hand, Rokitzki et al [24] reported higher α EAST values in groups of female handball players compared with male basketball players and wrestlers. Therefore, it cannot be excluded that the α EAST value depends on sex.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Fogelholm et al [10], although the α EAST values obtained by them were higher than in this study. On the other hand, Rokitzki et al [24] reported higher α EAST values in groups of female handball players compared with male basketball players and wrestlers. Therefore, it cannot be excluded that the α EAST value depends on sex.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes studies examining dietary intake of vitamin B-6 in athletes. Some studies report vitamin B-6 intakes by athletes that are less than recommended guidelines, especially female athletes with low energy intakes (51,75). For example, when dietary intakes of trained female cyclists were examined, more than a third consumed less than the RDA for vitamin B-6 (45).…”
Section: Vitamin B-6mentioning
confidence: 99%
“…In addition, Steen et al found that only 70% of female heavyweight rowers met the RDA for vitamin B-6 (83). A study of strength and speedpower German athletes found that more than 30% did not meet the dietary guidelines for vitamin B-6 for that country (1.8 mg/d male, 1.6 mg/d female) (75). However, Niekamp and Baer (62) documented better vitamin B-6 intakes in male cross-country runners with mean intake levels greater than the 1989 RDA.…”
Section: Vitamin B-6mentioning
confidence: 99%
“…Using the 1998 EAR, adequate dietary intakes for vitamin B 6 have been reported for female athletes with subclinical eating disorders (Beals and Manore 1998), master athletes (Beshgetoor and Nichols 2003), field athletes (Faber and Benadé 1991), recreational athletes (Joubert and Manore 2008), distance runners (Kaiserauer et al 1989;Manore et al 1989;Nieman et al 1989), cyclists (Keith and Alt 1991), runners with amenorrhea (Kopp-Woodroffe et al 1999), handball athletes (Rokitzki et al 1994c), and triathletes (Worme et al 1990). Historically, results are mixed in regards to vitamin B 6 intake among female athletes due to revised dietary recommendations.…”
Section: Dietary Intake and Status Of Vitamin B 6 In Active Adultsmentioning
confidence: 93%